How difficult can this be? understanding learning disabilities : frustration, anxiety, tension, the F.A.T. city workshop - Rosen, Peter; Lavoie, Richard D.; Eagle Hill School Outreach; Peter Rosen Productions; PBS Video ([Alexandria, VA] : Artwork PBS, 2004)
A group experiences life the way a learning disabled student does and learns methods of teaching and helping such students.
Experiencing frustration, anxiety & tension -- Processing -- Risk taking -- Visual perception -- Reading comprehension -- Effect of perception on behavior -- Visual motor coordination -- Oral expression -- Reading and decoding -- Auditory and visual capabilities -- Fairness -- Commentary.
Special features include a new interview with Richard Lavoie.
Cameras, Burleigh Wartes, Tony Cobbs ; editor, Harvey Kopel ; creative consultants, Janet Lavoie, Beryl Kaufman.
DVD.
Closed-captioned ; Spanish audio.
Keywords: Learning disabilities; Learning disabled children; Learning disabled children -- Education; Video recordings for hard of hearing people